STRATEGI PENGEMBANGAN USAHATANI SEMANGKA DALAM MENINGKATKAN DAYA SAING AGRIBISNIS - Maria Agustina Dua Nona; Fiator Nong; Sarlina Noni (Universitas Cokroaminoto Palopo, 2026)
Watermelon farming is a horticultural commodity with high economic value and strong market potential. This study aims to analyze the development strategy of watermelon farming to enhance agribusiness competitiveness at the Practice Garden of the Faculty of Food Technology, Agriculture and Fisheries, Universitas Nusa Nipa. The research method used is descriptive qualitative with a SWOT analysis approach. Data were collected through observation, interviews, and documentation. The results show that the business position is in quadrant I (SO), indicating strong internal strengths and external opportunities. Recommended strategies include utilizing fertile land, skilled labor, applying cultivation technology, and strengthening marketing to improve agribusiness competitiveness.